Caracterização da avifauna em áreas de transição agroecológica no assentamento Ipanema em Iperó-SP - Campos, Samara Cristina (2017)
This work aims to compare the composition and dynamics of birds in agricultural environments in different stages of agroecological transition and environments with conventional planting with the forest areas present in the Ipanema National Forest, located in the city of Iperó-SP. The methodology used was transect sampling by all areas in the early morning or late afternoon, once per month for two hours. Two areas were studied in the Ipanema National Forest and six agricultural areas belonging to the Ipanema settlement, three lots being in the process of agroecological transition, one in the agroecological process, and two lots that use only conventional practices, with the use of pesticides and fertilizers Chemicals. Between April 2015 and February 2016, after 160 hours of sampling, 2403 contacts were recorded (1752 contacts in the settlement lots, 634 in the trails of Flona de Ipanema), which sampled 150 bird species belonging to 43 families. The largest number of species occurred in Flona de Ipanema, on the Pedra Santa trail with 122 species, followed by 72 species in area 6 (agroecological planting) and 51 species on the Afonso Sardinha trail in Flona de Ipanema. The guild that stood out in all areas was the insectivorous, followed by omnivores in most areas. The richness of birds in the agricultural areas did not surpass those belonging to the native forest areas, however, the area with agroecological production, presented a greater wealth and abundance in relation to the other areas analyzed, evidencing that agroecological areas may present greater avifauna diversity, when compared to other types of plantation.